Natural resources and sustainable development - Peacock, Kathy Wilson (New York : Facts On File, 2008)
From the Publisher: Natural Resources and Sustainable Development is part of the Global Issues series, which is designed to be a first-stop resource for research on the key challenges facing the world today. Each volume contains three sections, beginning with an introduction that clearly defines the issue, followed by detailed case studies of the issue's impact in the United States and several other countries or regions. The second section draws together significant U.S. and international primary source documents, and the third section gathers useful research tools such as brief biographies, facts and figures, an annotated bibliography, and more. A foreword written by an expert in the field complements each volume. A chronology, glossary, and index provide additional help. There are more than 6 billion people living on Earth today, and the United Nations predicts this number will surge to 9.1 billion by the year 2050. However, the natural resources needed to sustain the world's population-including freshwater, arable land, and fossil fuels-are dwindling. In order to achieve sustainable development, the stress exerted on the environment by the world's population will have to be controlled through reduced rates of consumption. Natural Resources and Sustainable Development explores the impact that overconsumption has had on natural resources in the United States, China, India, Germany, and Brazil. It analyzes strategies that governments can use to reduce energy consumption and discusses the ongoing efforts to find alternative sources.
Foreword / Jeremy Carl -- Part 1: At Issue -- 1: Introduction -- 2: Focus on the United States -- 3: Global perspectives -- Part 2: Primary Sources -- 4: United States documents -- 5: International documents -- Part 3: Research Tools -- 6: How to research sustainable development -- 7: Facts and figures -- 8: Key players A to Z -- 9: Organizations and agencies -- 10: Annotated bibliography -- Chronology -- Glossary -- Index.
Includes bibliographical references (p. 303-340) and index.
Keywords: Natural resources -- Management; Sustainable development; Natural resources -- United States -- Management; Sustainable development -- United States